Nutrition Therapy for Stunting - Julius Anzar (Arkus, 2015)
Stunting is a decrease in height growth rate as measured by the height value by age under minus two standard deviations of the WHO child growth standards graph. In 2016 as many as 22.9% (154.8 million) of children under five years of age suffered from stunting, and Indonesia is in the 5th place of the country that suffers most from stunting. The leading cause of stunting is unbalanced nutritional factors in quantity and quantity during the growth period. Other causes are human factors; infant and child feeding practices, severe infections, subclinical infections, low birth weight babies and premature infants and social factors, such as household poverty, poor parenting, unresponsive eating practices, inadequate child stimulation, food insecurity, limited health services, access to clean water and sanitation. Children can be predicted to be stunting by measuring height periodically since birth. The most effective intervention to prevent stunting is to increase children’s diet quality. The Indonesian government role as a program and policymaker is to create a Stunting Intervention Framework, namely Specific Nutrition Interventions and Sensitive Nutrition Interventions. In conclusion, stunting can be predicted and can be prevented. Provision of MPASI by WHO recommendations that are timely, adequate, safe and are given in the proper manner is a specific nutrition intervention that can prevent stunting.